Innovative trends in recreation: aspects of psychoanalysis and art resources - Olga Kostikova; Svitlana Korsun; Irina Shaposhnikova; Yana Suvorova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: the problem of updating the art features of psychoanalytic concepts in the perspective of innovations in the recreation. Material & Methods: theoretical analysis and synthesis of domestic and foreign publications on the research problem. Results: analyzed current trends current research in the field of health and recreational activities. The paper considers the classical aspects of the art modification of psychoanalysis in the context of innovation strategies in recreation. Conclusions: theoretically probable positive effect of the implementation of the ideas of psychoanalysis and possibilities of art in productive innovation recreative process.